Improving reaction uniformity of high‐loading lithium‐sulfur pouch batteries - Hun Kim; Jae‐Min Kim; Ha‐Neul Choi; Kyeong‐Jun Min; Shivam Kansara; Jang‐Yeon Hwang; Jung Ho Kim; Hun‐Gi Jung; Yang‐Kook Sun (Carbon Energy)
Abstract Lithium‐sulfur batteries (LSBs) have garnered attention from both academia and industry because they can achieve high energy densities (>400 Wh kg–1), which are difficult to achieve in commercially available lithium‐ion batteries. As a preparation step for practically utilizing LSBs, there is a problem, wherein battery cycle life rapidly reduces as the loading level of the sulfur cathode increases and the electrode area expands. In this study, a separator coated with boehmite on both sides of polyethylene (hereinafter denoted as boehmite separator) is incorporated into a high‐loading Li‐S pouch battery to suppress sudden capacity drops and achieve a longer cycle life. We explore a phenomenon by which inequality is generated in regions where an electrochemical reaction occurs in the sulfur cathode during the discharging and charging of a high‐capacity Li‐S pouch battery. The boehmite separator inhibits the accumulation of sulfur‐related species on the surface of the sulfur cathode to induce an even reaction across the entire cathode and suppresses the degradation of the Li metal anode, allowing the pouch battery with an areal capacity of 8 mAh cm–2 to operate stably for 300 cycles. These results demonstrate the importance of customizing separators for the practical use of LSBs.